Inflammation, vitamin D and dendritic cell precursors in chronic kidney disease. (16th August 2016) - Paul, K; Franke, S; Nadal, J; Schmid, M; Yilmaz, A; Kretzschmar, D; Bärthlein, B; Titze, S; Koettgen, A; Wolf, G; Busch, M
Summary: Decreased blood dendritic cell precursors (DCP) count is linked with atherosclerotic disease, while reduction of circulating DCP is also seen in patients with chronic kidney disease (CKD). As poor vitamin D status could be linked to a compromised innate immune response, we hypothesized that vitamin D status might be involved in the decrease in circulating DCP in CKD. Moreover, the potential role of inflammation was considered. Circulating myeloid (mDCP), plasmacytoid (pDCP) and total DCP (tDCP) were analysed using flow cytometry in 287 patients with CKD stage 3. Serum 25(OH)D and 1, 25(OH)2D levels were measured using enzyme-linked immunosorbent assays (ELISA), interleukin (IL)-6, IL-10 and tumour necrosis factor (TNF)-α using cytometric bead array, C-reactive protein (CRP) using a high-sensitivity (hs) ELISA. Contrary to our hypothesis, there was no association between vitamin D levels and DCP, although their number was decreased significantly in CKD ( P  < 0·001). Instead, mDCP ( r  = −0·211) and tDCP ( r  = −0·188, ) were associated slightly negatively with hsCRP but positively with the estimated glomerular filtration rate (eGFR, r  = 0·314 for tDCP). According to multivariate linear regression, only higher hsCRP concentration and the presence of diabetes mellitus had a significant negative influence on DCP count ( P  < 0·03, respectively) but not vitamin D, age and eGFR. A significant impact of vitamin D on the reduction of circulating DCP in CKD 3 patients can be neglected. Instead, inflammation as a common phenomenon in CKD and diabetes mellitus had the main influence on the decrease in DCP. Thus, a potential role for DCP as a sensitive marker of inflammation and cardiovascular risk should be elucidated in future studies. Graphical Abstract: